Hydrological Season Can Have Unexpectedly Insignificant Influences on the Elevational Patterns of Functional Diversity of Riverine Macroinvertebrates - Qingyi Luo; Ming-Chih Chiu; Lu Tan; Qinghua Cai (Biology, 2022)
Spatial biodiversity is a key issue in biogeography for the explorations of biological origin and diversification. However, seldom studies have addressed the temporal changes in spatial patterns of biodiversity. We explored the taxonomic and functional diversities of riverine macroinvertebrates in central China, with the elevational gradient, in different seasons in a normal climate year (i.e., no extreme anomalies in the annual precipitation or average annual temperature). The air temperature and streamflow discharge were decreased monotonically with the increase of elevation both in the dry and wet seasons. In addition, the total nitrogen had no significant change with the increase of elevational gradient in the dry season but showed a monotonically decreasing pattern in the wet season. The total phosphorus showed a monotonically decreasing pattern with the elevational gradient in the dry season but had no significant change in the wet season. The spatial pattern of taxonomic diversity of macroinvertebrates along the elevational gradient showed complex patterns, but the functional diversity had either the unimodal or monotonically decreasing pattern. In addition, the functional diversity with the elevational gradient had similar patterns between the dry and wet seasons. Further analysis of the elevational pattern in different seasons is an important basis for understanding the status quo of functional diversity and formulating countermeasures for biodiversity conservation.